2021
DOI: 10.1186/s12913-021-07053-4
|View full text |Cite
|
Sign up to set email alerts
|

Quality of antenatal care and its sociodemographic determinants: results of the 2015 Pelotas birth cohort, Brazil

Abstract: Background Inadequate antenatal care (ANC) has been associated with adverse pregnancy outcomes. ANC quality is considered a key component of the right to health and a route to equity and dignity for women and their children. Although ANC coverage is relatively high in Brazil, there are revealed some health disparities when coverage is examined by socio-demographic determinants. In this study we evaluated ANC quality and its socio-demographic determinants using data from the 2015 Pelotas birth c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
21
1
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 38 publications
9
21
1
9
Order By: Relevance
“…Other studies found values close to the findings in this study, with percentages ranging from 86.2% to 89% (19)(20) . The result of this study is expressive, especially if we consider the mean absenteeism of 1.7 consultations per woman, which reveals effectiveness in follow-up and bonding of pregnant women despite the absences, although it also raises the discussion about the reasons attributed to such absences and what measures could be adopted to ensure optimization of care in the care network.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Other studies found values close to the findings in this study, with percentages ranging from 86.2% to 89% (19)(20) . The result of this study is expressive, especially if we consider the mean absenteeism of 1.7 consultations per woman, which reveals effectiveness in follow-up and bonding of pregnant women despite the absences, although it also raises the discussion about the reasons attributed to such absences and what measures could be adopted to ensure optimization of care in the care network.…”
Section: Discussionsupporting
confidence: 91%
“…A cohort study carried out in northeastern Brazil about prenatal care content inadequacy used a hierarchical model for analysis that considers characteristics that are close to what was proposed in this research, having as adequacy variables the beginning of prenatal care, the number of consultations, vaccination, laboratory tests and obstetric procedures, whose results showed that the recommended criteria were not incorporated into clinical practice (23) . Other investigations on the prenatal care process indicate a prevalence of around 24% for overall adequacy, including as procedures, exams and orientations received during prenatal care in the basic health network as variables (19)(20) . The findings of such studies corroborate the results presented here, which show even higher prevalence of inadequacy in the second and third trimesters of pregnancy, when compared to the first trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Outros estudos encontraram valores próximos aos achados nesta pesquisa, com percentuais variando entre 86,2% e 89% (19)(20) . O resultado do presente estudo é expressivo, especialmente se considerarmos o absenteísmo médio de 1,7 consultas por mulher, o que revela eficácia no seguimento e vinculação das gestantes apesar das faltas, embora levante também a discussão sobre as razões atribuídas a tais ausências e quais medidas poderiam ser adotadas para garantir otimização dos atendimentos na rede assistencial.…”
Section: Discussionunclassified
“…Um estudo de coorte realizado no nordeste brasileiro acerca da inadequação do conteúdo da assistência pré-natal utilizou um modelo hierarquizado para análise que considera características que se aproximam do proposto nesta pesquisa, tendo como variáveis de adequação o início do pré-natal, o número de consultas, a vacinação, os exames laboratoriais e os procedimentos obstétricos, cujos resultados demostraram que os critérios preconizados não foram incorporados à prática clínica (23) . Outras investigações sobre o processo de cuidado no pré-natal apontam prevalência em torno de 24% para adequação global, incluindo como variáveis procedimentos, exames e orientações recebidas durante o pré-natal na rede básica de saúde (19)(20) . Os achados de tais pesquisas corroboram os resultados aqui apresentados, que mostram ainda maiores prevalências de inadequação no segundo e terceiro trimestres gestacionais, quando comparados ao primeiro trimestre da gestação.…”
Section: Discussionunclassified
“…According to the Pelotas cohort study, adolescents were more likely to experience inadequate quality of antenatal care. 29 In addition, the coverage was lower in younger women. The proportion of adolescents with more than six visits to the antenatal clinic were 74.1%-these were 68.7%, 90.1%, and 91.8% for women aged 20-29 years, 30-39 years, and 40 years and over, respectively.…”
Section: Discussionmentioning
confidence: 99%